Diet transformation in Africa: The case of Ethiopia - Hassen, Ibrahim Worku; Dereje, Mekdim; Minten, Bart; Hirvonen, Kalle (International Food Policy Research Institute, 2016)
Africa's food systems are changing fast amid rapid economic growth, emerging urbanization, and structural transformation. In this study, we use four rounds of nationally representative data from Ethiopia to examine changes in household food consumption patterns over a period of unprecedented economic growth. We find that while there is a general decline in the share of food in the total consumption basket of households in Ethiopia, food quantities and intake of calories have increased considerably over the period 1996 to 2011. This was mostly driven by improvements in household incomes, as shown using decomposition analysis. Furthermore, the content of the food basket is changing with a gradual shift towards high-value foods, such as animal products, fruits and vegetables, and processed foods. However, irrespective of the level of income, a heavy focus on starchy staples in the Ethiopian diet remains. Overall, this diet transformation has important implications for the food security debate and for agricultural and food policy in the country.